2023
DOI: 10.3390/brainsci13070990
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Synthetic Cannabinoids in K2/Spice: A Systematic Review

Abstract: (1) Background: Synthetic cannabinoids (SCs) are emerging drugs of abuse sold as ‘K2’, ‘K9’ or ‘Spice’. Evidence shows that using SCs products leads to greater health risks than cannabis. They have been associated with greater toxicity and higher addiction potential unrelated to the primary psychoactive component of marijuana, Δ9-tetrahydrocannabinol (Δ9-THC). Moreover, early cases of intoxication and death related to SCs highlight the inherent danger that may accompany the use of these substances. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…The use of synthetic and semi-synthetic cannabinoids has been associated with a variety of adverse effects, including anxiety, agitation, hallucinations, seizures, and, in extreme cases, severe risks to life. However, the long-term effects of repeated use are poorly understood [39]. Fatalities associated with synthetic cannabinoids have been reported [40,41].…”
Section: Synthetic and Semi-synthetic Cannabinoidsmentioning
confidence: 99%
“…The use of synthetic and semi-synthetic cannabinoids has been associated with a variety of adverse effects, including anxiety, agitation, hallucinations, seizures, and, in extreme cases, severe risks to life. However, the long-term effects of repeated use are poorly understood [39]. Fatalities associated with synthetic cannabinoids have been reported [40,41].…”
Section: Synthetic and Semi-synthetic Cannabinoidsmentioning
confidence: 99%
“…Its chemical structure is most similar to APINACA (AKB48) and 5F-APINACA (5F-AKB48), which are potent agonists of both the CB1 receptor and the CB2 receptor [ 16 ]. 4F-ABUTINACA appeared in Asia in 2020, but no data are available about its pharmacological properties [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its chemical structure is most similar to APINACA (AKB48) and 5F-APINACA (5F-AKB48), which are potent agonists of both the CB1 receptor and the CB2 receptor [16]. 4F-ABUTINACA appeared in Asia in 2020, but no data are available about its pharmacological properties [17][18][19]. Based on in vitro biological activity assessment at cannabinoid type 1 (CB1) receptor via its interaction with β-arrestin 2, the potency and efficacy of MDMB-4en-PINACA is similar to that of their structural analogs 4F-MDMB-BINACA and 5F-MDMB-PINACA.…”
Section: Introductionmentioning
confidence: 99%
“…Crucial information about these substances that is typically lacking in the early periods of use regards their potential toxic effects. The systematic review by de Oliveira et al [ 7 ] focuses on synthetic cannabinoids. Originally synthesized for research purposes, these authors found that their main use was as drugs of abuse mixed with other various substances and herbs.…”
mentioning
confidence: 99%